Allopachria yiae sp. n. from Chongqing, China (Coleoptera: Dytiscidae: Hydroporinae) - Bian, Dongju; Guo, Cheng; Ji, Lanzhu (Zootaxa, 2013)
The genus Allopachria Zimmermann, 1924 (Hydroporinae: Hyphydrini) with a rich diversity of species occurs throughout southeastern Asia. Recently eight new species were reported from China, Laos and Indonesia by Wewalka (2010) and another four new species from China were added by Bian & Ji (2010, 2012). In the most recent version of the World Catalogue of Dytiscidae, Nilsson (2013) listed 45 species, 27 of which are known from southern parts of China (cf. Nilsson & Hájek 2013). The study of Allopachria specimens recently collected in the Chongqing Municipality revealed another new species, raising the number of Allopachria to 46. Allopachria yiae sp. n. is described, illustrated and compared with related species. It is the first species of the genus recorded from Chongqing.